Preparation of polyurethane–alginate/chitosan core shell nanoparticles for the purpose of oral insulin delivery. (July 2017) - Bhattacharyya, Aditi; Mukherjee, Debarati; Mishra, Roshnara; Kundu, P.P.
Graphical abstract: Highlights: Synthesis of polyurethane using depolymerised polyethylene terephthalate. Insulin loaded polyurethane-alginate/chitosan core-shell nanoparticles preparation. Oral delivery of insulin loaded core-shell nanoparticles in animal model. Toxicity assessment of these core-shell nanoparticles in animal model. Abstract: Waste polyethylene terephthalate (PET) is depolymerized through glycolysis and the glycolyzed product, bis (2-hydroxyethylene) terephthalate (BHET) is utilized in the synthesis of polyurethane as diol. Polyurethane (PU) is incorporated in a core- shell nanoparticle formulation along with alginate (ALG) and chitosan (CS) to develop an efficient oral insulin delivery vehicle. Fourier transform infrared (FT-IR) spectrums of the polyurethane-alginate/chitosan (PU-ALG/CS) nanoparticles confirm the presence of all elements distinctly. Nanoparticles of average particle size 90–110 nm are clearly visible from the images of scanning electron microscope (SEM) and transmission electron microscope (TEM). Unique characteristics of insulin loaded PU-ALG/CS nanoparticles are noticed in both in vitro and in vivo studies. More than 90% insulin encapsulation efficiency, sustained swelling, controlled insulin release from mucoadhesive nanoparticle formulation are the major causes of long term hypoglycaemic effects in diabetic mice and improved insulin bioavailability (10.36%). PU-ALG/CS nanoparticles are also found to be safe, according to the acute toxicity studies.